Rotavirus infections in children in Turkey: A systematic review. (4th December 2018) - Tapisiz, Anil; Bedir Demirdag, Tugba; Cura Yayla, Burcu Ceylan; Gunes, Cemalettin; Ugraş Dikmen, Asiye; Tezer, Hasan; Baran Aksakal, Nur; Bozdayi, Gulendam; Ozkan, Secil
Summary: We aimed to describe rotavirus epidemiology and clinical findings including extraintestinal manifestations in a setting that has yet to introduce rotavirus vaccines in the national immunization program. A literature search was performed by using the key words "Turkey" and "rotavirus." Ninety‐eight studies published between 1987 and 2016 including epidemiological, clinical, and genotypical data at least 1 year duration were included. There were a total of 117 741 children with diarrhea and 26 566 rotavirus gastroenteritis with a median detection rate 31.8% (95% CI, 31.3‐32.4) under 5 years of age. The rate of dehydration was 47% (95% CI, 23.4‐91.6). There were 328 cases reported to be presenting with a various complication related to rotavirus in 2750 children in eight studies. The overall complication rate was 11.7% (95% CI, 10.7‐12.9). The cumulative incidence of the most common genotypical combinations circulating worldwide was only 59.7% (G9[P8], 25%; G1[P8], 22%; G2[P4], 5.6%; G3[P8], 2.6%; G4[P8], 4.5%) whereas mixed, untypeable, and other genotypes were 2.4%, 15%, and 22.9% respectively. Our results point out the importance of rotavirus vaccination by presenting that rotavirus may cause severe complications besides severe gastroenteritis. The role of strain diversity in the variability of clinical presentations of rotavirus infections needs to be further investigated.